Suitability of a lumped rainfall–runoff model for flashy tropical watersheds in New Caledonia. Issue 11 (18th August 2018) - Desclaux, Térence; Lemonnier, Hugues; Genthon, Pierre; Soulard, Benoit; Le Gendre, Romain
ABSTRACT: The GR4H lumped hourly rainfall–runoff model was assessed for its integration in a ridge-to-reef modelling framework. Particular attention was paid to rainfall representation, robustness of parameter estimates and ability to reproduce the main runoff features. The study was conducted in four tropical mountainous watersheds in New Caledonia, which are exposed to intense rainfall events, large annual climatic variations triggered by El Niño oscillation, and wildfires. The inverse distance and elevation weighting algorithm outperformed other classical rainfall interpolation methods under data-limited conditions. The time span of data needed for robust calibration was site specific and varied from 6–7 years to 10 years, which may be linked to El Niño events and to wildfires. With sufficient data, simulation quality was equivalent during the calibration and validation periods. The GR4H model was generally able to simulate both flash floods and large annual variations. The model was more reliable when simulating wet years and watersheds not subject to land-cover changes.